Recurrent Abdominal Pain in Children - Sulaiman Yusuf; Badriul Hegar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2006)
Recurrent abdominal pain is one of the most common symptoms found in children. Description of abdominal pain is important in determining the etiologic cause. Organic pain must be ruled out first before suspecting psychogenic cause of pain. However, Children and infant are likely having difficulties in describing abdominal pain. Referred pain may lead to misdiagnosis. Alarm symptoms of abdominal pain are important indices and must be recognized. Careful and complete anamnesis and physical examination play critical role in management approach of recurrent abdominal pain in children and determine whether medical therapy only or combination with surgical intervention is considered necessary. Keywords: recurrent abdominal pain, children, alarm symptom